Unia Europejska wobec nowych tworów państwowych (Casus Kosowa, Abchazji i Osetii Południowej) - Potyrała, Anna (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2010)
When the European Union member states’ attitude to Kosovo is not uniform, the EU’s prestige and influence on the international arena deteriorates. As far as the issue of Abkhazia and South Ossetia is concerned, the EU’s activities show that mere expressions of interest in the matter and providing ‘apolitical’ financial aid does not contribute to solving this thorny international problem, and undermines the international position of the European Union unless it is coupled with clear and precise political aims, the operations of institutions with a strong mandate or a process of active negotiation. Once more, member states show that the concept of the Common Foreign and Security Policy, supported among others by the European Neighborhood Policy, does not have firm foundations.